International Perspectives on Teachers and Lecturers in Technical and Vocational Education
XIII, 334 p.
Keywords: This book provides insight into the history and current status of teaching in technical and vocational education across a broad range of countries. It contains studies of the profiles of teachers and lecturers and their educational practices in: Germany, Brazil, Denmark, China, France, Japan, Norway, Turkey, the UK and the USA. All chapters follow a common structure making it easy for the reader to focus on specific aspects. An overarching introduction embeds the content of the book into the current global context of Technical and Vocational Education and Training.